Kadar Protein Dan Kualitas Tempe Komposisi Koro Benguk Dan Bekatul Pada Variasi Daun Pembungkus - WIDIYANTI, ANA; Suryani, M.Sc., Dra. Titik (2016)
Mucuna tempe is tempe made from raw materials "koro benguk", which had complete nutritional content. Rice bran derived from rice mill byproduct, which had high protein content. Innovation mucuna tempe with a mixture of rice bran by using a wrapper leaf banana leaves, hibiscus leaves and teak leaves, each of which has a different characteristics. The purpose of this research to determine the levels of soluble protein and quality tempe composition "koro benguk" and rice bran of variation wrapper leaf. This research used an experimental method Completely Randomized Design (CRD) two factors, one is a composition ratio "koro benguk": rice bran (A0 = 100g:0g, A1 = 180g:20g, A2= 170g:30g and A3= 160g:40g) and factor 2 that leaf wrapper (B1 = banana leaves, B2 = teak leaves and B3= hibiscus leaves) with 12 treatment. The results showed that the highest levels of soluble protein in the treatment of A3B2 ("koro benguk" 160g : rice bran 40g) of 11.75 g/l and the lowest in the A0B3 ("koro benguk" 200g : rice bran 0g) of 3.9 g/l. The quality of mucuna tempe with a mixture of rice bran and different wrapper leaf texture produces loud, the flavor of fresh tempe and the colour white full.